Health Education In Order To Prevent And Transmit Covid-19 In The Elderly Through Audio Visuals - Fatimah Fatimah; Iswenti Novera; Yenni Elfira; Irwadi Irwadi; Ikhsan Amran; Leo Agustino (Journal of Public Health Indonesian, 2024)
Coronavirus Disease 2019 (Covid-19) has caused health problems worldwide with increasing morbidity and mortality that can infect all age groups with the highest mortality rate of 95% in the vulnerable age group, namely the elderly with an age range of >60 years. The rapid increase and addition of deaths due to Covid-19 has had a negative impact on every aspect of life with changes in new habits from social, economic, religious and psychological aspects. One of the efforts that can be made to prevent the transmission of Covid-19 is to improve Clean and Healthy Living Behavior. Counseling on clean and healthy living behavior was carried out at the Tresna Werdha Sabai Nan Aluih Sicincin social institution on November 12, 2021 with elderly participants who were in the social institution. The counseling method used was using poster and leaflet media and conducting demonstrations in the form of showing Minang language caricature videos related to health education in the context of preventing and transmitting Covid-19. The methods applied can focus the attention of training participants to be able to focus and easily understand information. The results of the counseling showed that 97% of the elderly understood and knew how to live a clean and healthy lifestyle to avoid contracting Covid-19.